Investment value of changes in analysts’ consensus-recommendations on JSE Top 40 shares - Soni, Vilosha (My University, 2014)
The aim of this study was to determine whether there was investment value to trading on upgrade and downgrade changes in analysts’ consensus. An event study was undertaken on JSE Top 40 shares to measure the sensitivity of cumulative average abnormal returns (CAARs) to changes in analysts’ consensus for the period 2001 to 2012. A comprehensive literature review was conducted to establish the study approach employed and select the best available methodology to model expected market returns. Limited evidence of the semi-strong form of market efficiency was shown for the JSE, with JSE Top 40 share prices and therefore returns responding quickly to changes in analysts’ consensus upgrades. Changes in analyst consensus downgrades, however, were met with longer post event drift. Short-term trading and profit opportunities could exist, mostly for institutional investors acting on changes in consensus upgrades and downgrades. High transaction costs, however, would leave very few profitable trading opportunities for smaller private investors. Smaller investors should be cautioned against trading on analyst recommendations alone, without paying attention to other signals, as signs of analyst bias (including herding) were found in this sample. Overall the study provides evidence that analysts do add value from the technical and fundamental analysis that they conduct by uncovering valuable, new information to the market, in line with the market efficiency view of Grossman and Stiglitz (1980). This could allow mainly, institutional investors, trading opportunities to earn abnormal returns when considerable changes to analyst consensus on JSE Top 40 companies are made
MBA thesis
Keywords: Johannesburg Securities Exchange; Investment analysis